Re-conceptualising graduate employability: the importance of pre-professional identity. Issue 5 (2nd September 2016) - Jackson, Denise
ABSTRACT: Despite efforts to broaden the concept of graduate employability, there remains an overarching focus on developing industry-relevant employability skills. The skills-based approach is, however, too narrow and does not fully capture the complexity of graduate work-readiness. This paper argues for the redefining of graduate employability by embracing pre-professional identity (PPI) formation. PPI relates to an understanding of and connection with the skills, qualities, conduct, culture and ideology of a student's intended profession. The 'communities of practice' model is drawn upon to demonstrate how PPI can be developed during university years. Here, a student makes sense of his/her intended profession through multiple memberships and differing levels of engagement with various communities within higher education's 'landscape of practice'. Example communities include professional associations, student societies, careers services and employers. Implications for stakeholders are discussed.